Gregory Baum’s Contribution to The Ecumenist - Schweitzer, Donald (Théologiques, 2021)
This article explores Gregory Baum’s contributions both as an editor and as a theologian to the journal The Ecumenist, which he founded in 1962. It explores the original orientation that he set for it of forwarding ecumenism, then how this changed in the 1970s, when The Ecumenist became a journal devoted to critical theology. It then examines the contributions Baum made to this journal through his own writing. This provided a critical Christian witness that sought to keep pace with the changing faces of evil in Western societies and churches and to relate Jesus to these in liberating ways.